2005
DOI: 10.1093/geronb/60.special_issue_2.s15
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Change in the Social Stratification of Aging and Health Over the Life Course: Evidence From a Nationally Representative Longitudinal Study From 1986 to 2001/2002 (Americans' Changing Lives Study)

Abstract: The results indicate that understanding and alleviating social disparities in health are both theoretically and methodologically quintessential problems of life course analysis and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
304
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 340 publications
(345 citation statements)
references
References 34 publications
29
304
5
2
Order By: Relevance
“…Indeed, evidence has shown that the effects of socioeconomic disparities on health may have the most impact earlier in life, perhaps due to mortality selection. [30][31][32] Since SSS comes from a person's assessment of his or her own station, it might be a domain that reflects the cumulative impact of an individual's shifting SES throughout his or her lifetime. A growing literature also links neighborhood socioeconomic characteristics to the health of its residents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evidence has shown that the effects of socioeconomic disparities on health may have the most impact earlier in life, perhaps due to mortality selection. [30][31][32] Since SSS comes from a person's assessment of his or her own station, it might be a domain that reflects the cumulative impact of an individual's shifting SES throughout his or her lifetime. A growing literature also links neighborhood socioeconomic characteristics to the health of its residents.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral and lifestyle factors, such as eating habits, tobacco use and physical activity have been identified as important correlates for health (Lee et al 2012). Several studies have confirmed the association between low SES and adverse health outcomes (Braveman & Gottlieb 2014, House, Lantz & Herd 2005. Health disparity research has also been conducted from a life course perspective, taking into account factors from the past and the present, thus reflecting resources and risks affecting health over a longer period of time (Braveman 2014b).…”
Section: Disparitymentioning
confidence: 99%
“…Other measures of SES, such as income, have also been associated with health status in old age (Dahl & Birkelund 1997). A social gradient has also been seen in the compression of morbidity and functional limitations (House, Lantz & Herd 2005). Childhood SES also has an effect on mortality (Giesinger et al 2014).…”
Section: Socioeconomic Status In Old Agementioning
confidence: 99%
See 2 more Smart Citations